Dietary pattern in pregnancy and risk of gestational diabetes mellitus (GDM). Issue 3 (May 2018) - Zareei, Saeideh; Homayounfar, Reza; Naghizadeh, Mohammad mehdi; Ehrampoush, Elham; Rahimi, Maryam
Abstract: Aim: Among the most common metabolic disorders during pregnancy is gestational diabetes mellitus (GDM). This research was conducted to examine the dietary pattern in women with GDM. Material and methods: In this case-study, 204 pregnant women (104 cases and 100 control women) were chosen through convenient sampling and random sampling. The subjects' food intakes were assessed using semi-quantitative food frequency questionnaire, while their activities evaluated by physical activity questionnaire. Anthropometric indices were measured based on standard instructions, and the body mass index was calculated. The dietary patterns were determined using principal component analysis and its relationship with preeclampsia was tested using logistic regression method. Results: Unhealthy and healthy dietary patterns were found among the pregnant women. In the unhealthy group, after modifying the effect of confounding variables, a significant relationship was observed between dietary pattern and having gestational diabetes (OR = 2.838, 95% CI:1.039–7.751). In the healthy group, on the other hand, the people in the fourth quartile had 149% and 184% higher chance not to catch gestational diabetes before and after modification with confounders, respectively (OR = 0.284, 95% CI:0.096–0.838), when compared with people in the first quartile. Conclusion: The findings indicated that selection of foods including fruits, vegetables, low-fat dairies, etc. as healthy dietary pattern is associated with diminished risk of GDM among pregnant women. Determining healthy dietary pattern during pregnancy, considering the foods consumed among pregnant women, as a useful and practical guide during this period can be publicized for training and nutritional interventions.